A rapid and simple chitinase assay to screen tea genotypes for resistance against blister blight - Nisha, S.N.; Prabu, G.R.; Mandal, A.K.A. (Journal of Plantation Crops, 2014)
Plant naturally responds to fungal attack by a complex network of defense mechanisms. Among these, production of pathogenesis related (PR) proteins is an important mode of resistance against pathogen invasion. Chitinase is one such PR protein and a potent biomarker for the identification of promising resistant germplasm. In this study, Gram’s iodine based detection assay for chitinase production in tea cultivars has been attempted to screen and validate the data available on the resistance level of the cultivars against blister blight disease. Small wells in the glycol-chitin-agarose/agar plates were loaded with enzyme extract and flooded with Gram’s iodine after 24h. The glycol-chitin formed a bluish complex with iodine, whereas the areas around the wells showed a sharp and distinct clearance zone, against the blue background. The diameter of the zone increased with increased amount of chitinase present in the sample. These observations were validated with field data on blister blight disease incidence in these cultivars and discussed. The new approach is an easy, reproducible, cost effective, user and environmental friendly qualitative method for rapid screening of the tea cultivars in breeding program.